Prevalence and outcome of patients with cancer and acute coronary syndrome undergoing percutaneous coronary intervention: a BleeMACS substudy. Issue 7 (1st October 2018) - Iannaccone, Mario; D'Ascenzo, Fabrizio; Vadalà, Paolo; Wilton, Stephen B; Noussan, Patrizia; Colombo, Francesco; Raposeiras Roubín, Sergio; Abu Assi, Emad; González-Juanatey, José Ramón; Simao Henriques, Jose Paulo; Saucedo, Jorge; Kikkert, Wouter J; et al.
Abstract: Background: The prevalence and outcome of patients with cancer that experience acute coronary syndrome (ACS) have to be determined. Methods and results: The BleeMACS project is a multicentre observational registry enrolling patients with acute coronary syndrome undergoing percutaneous coronary intervention worldwide in 15 hospitals. The primary endpoint was a composite event of death and re-infarction after one year of follow-up. Bleedings were the secondary endpoint. 15, 401 patients were enrolled, 926 (6.4%) in the cancer group and 14, 475 (93.6%) in the group of patients without cancer. Patients with cancer were older (70.8±10.3 vs. 62.8±12.1 years, P <0.001) with more severe comorbidities and presented more frequently with non-ST-segment elevation myocardial infarction compared with patients without cancer. After one year, patients with cancer more often experienced the composite endpoint (15.2% vs. 5.3%, P <0.001) and bleedings (6.5% vs. 3%, P <0.001). At multiple regression analysis the presence of cancer was the strongest independent predictor for the primary endpoint (hazard ratio (HR) 2.1, 1.8–2.5, P <0.001) and bleedings (HR 1.5, 1.1–2.1, P =0.015). Despite patients with cancer generally being undertreated, beta-blockers (relative risk (RR) 0.6, 0.4–0.9, P =0.05), angiotensin-converting enzyme inhibitors/angiotensin receptor blockers (RR 0.5, 0.3–0.8, P =0.02), statins (RR 0.3, 0.2–0.5, P <0.001) and dual antiplatelet therapy (RR 0.5, 0.3–0.9, P =0.05) were shown to be protective factors, while proton pump inhibitors (RR 1, 0.6–1.5, P =0.9) were neutral. Conclusion: Cancer has a non-negligible prevalence in patients with acute coronary syndrome undergoing percutaneous coronary intervention, with a major risk of cardiovascular events and bleedings. Moreover, these patients are often undertreated from clinical despite medical therapy seems to be protective. Registration: The BleeMACS project (NCT02466854).